The impact of intestinal transplantation on quality of life - Ambrose, T; Holdaway, L; Smith, A; Howe, H; Vokes, L; Vrakas, G; Reddy, S; Giele, H; Travis, SPL; Friend, PJ; Allan, PJ (Elsevier, 2019)
Introduction: Intestinal failure (IF) and intestinal transplant (ITx) are associated with poor quality of life (QoL). Disease-specific assessment of QoL for IF and ITx is challenging, owing to the different problems encountered. We have sought to compare QoL pre-ITx with post-ITx and have compared generic QoL with a stable IF population.